Continuous improvement and business sustainability in companies of an emerging market: Empirical analysis - César A. Bernal-Torres; Luis Paipa-Galeano; Yavar Jarrah-Nezhad; Luis M. Agudelo-Otálora; Javier Millán (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The article analyses the impact of continuous improvement (system and teams) on business sustainability dimensions (social, environmental, operational and financial) as a competitive strategy to create value for all stakeholders in emerging economy context. Design/methodology/approach: The data collected is from 120 companies of different sizes and 13 different industrial sectors such as food, energy, health, financial services, and logistics in Colombia. The design of multivariate logistic regression is to identify the critical aspects of the continuous improvement practices that significantly affect the dimensions of business sustainability. Findings: The analysis shows that from continuous improvement aspects (system and teams), employee involvement, human talent maintenance, training, and evaluation accompanied by feedback impact business sustainability. These elements impact financial and operational dimensions significantly but in the environmental and social aspects with less intensity. Research limitations/implications: Research is limited to the general sustainability analysis applying resource-based strategy in Colombia. Practical implications: Generate overall awareness of the importance of the equilibrium of sustainability dimensions in strategic planning and implementation in emerging economies. Originality/value: This work applies an empirical study to establish the impact of continuous improvement (system and teams) on each of the business sustainability dimensions (social, environmental, operational and financial) in companies of emerging economies.
Keywords: 650; Business sustainability; continuous improvement; logistic regression model; work teams